Catalytic Efficiency of Red Mud for the Degradation of Olive Mill Wastewater through Heterogeneous Fenton’s Process - Domingues, Eva (2019)
Olive mill wastewater is a challenging e uent, especially due to its toxicity related to the presence of phenolic compounds. Fenton’s process was analysed on the abatement of phenolic acids typically found in this kind of e uents. To overcome the main drawback of Fenton’s process, a waste from the aluminium industry commonly called red mud was used as a heterogeneous source of iron. The adsorption of simulated e uent on the red mud was negligible. Therefore, the degradation of phenolic acids during Fenton’s process was due to oxidation by hydroxyl radicals. The amount of red mud and hydrogen peroxide were optimized regarding phenolic acids degradation. The optimal conditions leading to the highest removal of contaminants (100% of phenolic acids degradation and 25% of mineralization after 60 min of reaction) were 1 g/L of catalyst and 100 mg/L of hydrogen peroxide. The possibility of recovering treated water for agricultural purposes was evaluated by assessing the toxic impact over a wide range of species. The toxicity observed for the treated samples was mainly related to the residual hydrogen peroxide remaining after treatment.